Monitoring the Effects of Sea Level Rise on some Soil Properties Related to Salt Affected Soils in Agricultural Areas of Lower Central Plain, Thailand - Phankamolsil, Napaporn (AGRIVITA, Journal of Agricultural Science, 2021)
The research was implemented to monitor the effects of sea level rise on some soil properties associated with salt affected soils in agricultural areas on the Lower Central Plain, Thailand and determine the severity of salt impact during different periods in these areas. To achieve these goals, soil samples from 11 locations were selected for investigation. All soils were deep, poorly drained, mainly fine textured, and low developed. The soil moisture ranged from 20.84-79.04%. Soil electrical conductivity (ECe) varied substantially between locations, depth levels, and periods of soil sampling, ranging from 0.21-4.42 dS/m. The sodium adsorption ratio (SAR) of these soils during the periods of soil sampling was rather higher than 13 in either some or all layers of the soil profiles, ranging from 6.80-41.89. These results suggested that many of the study locations were affected by salts and all sites could be classified as sodic soils with the classification increasing to saline-sodic soils in locations N4 in April, N5 in March, July and August, and P4 in March 2018. Thus, during these occasions, it was possible that the increased salt levels were due to the rising sea level compared to during May and June when there was high precipitation.